Unilateral Functional Uterine Horn with Non Functioning Rudimentary Horn and Cervico-Vaginal Agenesis: Case Report (Bangladesh Journal of Medical Science, 2014)
Developmental anomalies involving Mullerian ducts are one of the most fascinating disorders in Gynaecology. The incidence rates vary widely and have been described between 0.1-3.5% in the general population. We report a case of a fifteen year old girl who presented with primary amenorrhea and lower abdomen pain, with history of instrumentation about two months back. She was found to have abdominal lump of sixteen weeks size uterus. On examination vagina was found to be represented as a small blind pouch measuring 2-3cms in length. A rectovaginal fistula (2x2 cms) was also observed. Ultrasonography of abdomen revealed bulky uterus (size 11.2x6 cm) with 150 millilitre of collection. Adiagnosis of hematometra with iatrogenic fistula was made. Vaginal drainage of hematometra was done which was followed by laparotomy. Peroperatively she was found to have a left side unicornuate uterus with right side small rudimentary horn. Left fallopian tube and ovary showed dense adhesions and multiple endometriotic implants. Both cervix and vagina were absent. Total abdominal hysterectomy was done and rectovaginal fistula repaired. The present case is reported due to its rarity as it involved both mullerian agenesis with cervical and vaginal agenesis along with disorder of lateral fusion. This is an asymmetric type of mullerian duct development in which arrest has occurred in different stages of development on two sides. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17500 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 101-104